Dinamika Pelestarian Kesenian Senjang di Kabupaten Batang Hari Provinsi Jambi - Febby Febriyandi YS (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
Senjang is a Malay musical art found in the provinces of South Sumatra and Jambi. In South Sumatra, the existence of senjang is well maintained. This condition is achieved by combining senjang with modern musical instruments. Whereas in Jambi, senjang has been in decline since the 1990s. The artists have made various conservation efforts to no avail, and senjang in Jambi remains under threat of extinction to this day. Through a qualitative methods this study found that the decline of senjang in Jambi was caused by changes in people's livelihoods that changed the pattern of work organization in agriculture; changes in interest in music; and changes in social customs. The artists have made conservation efforts for the last twenty years, but to no avail due to obstacles arising from differences in interests with the local government. On the one hand, the artists want to add elements of dance, change musical instruments and songs to keep up with changes in people's musical interests, but the local government wants the use of musical instruments and traditional songs to be maintained in order to build regional cultural identity.